FEATURES OF EDUCATIONAL SERVICES IN MODERN CONDITIONS (Archive of Conferences, 2021)
Based on the study of scientific literature, the article defines the concepts of "education", "service", "educational services", reveals the distinctive features and characteristics of educational services. The author reveals the role and place of educational services in the information society.